Bluetooth Technology: An Exploratory Study of the Analysis and Implementation Frameworks - Mehta, Akshay; Kumar, Alok (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2014)
Bluetooth is still a relatively new technology to the wireless world. It is designed for wireless communication between a wide variety of different Bluetooth enabled devices; from computers and PDAs to GPS systems and heart monitoring devices. There are a growing number of companies continually adopting this technology. As Bluetooth becomes a standard feature in many products that we use everyday, it seems that the use of the technology will grow even faster in the future. This paper provides an analysis of the technology’s features and how companies should go about deciding if they should adopt Bluetooth or another wireless alternative. First, the paper talks about what Bluetooth is and how it compares with other wireless standards. It then goes into an analysis of how feasible integrating Bluetooth into a business would be, and how some industries are already using the technology. These case studies are followed by a look at what steps need to be taken through the implementation cycle, and deciding what technology makes a better fit for a business. The paper ends with a look at the pros and cons of Bluetooth, as well as a look into what the future may hold for this technology.